The successful accomplishment of nutritional and clinical outcomes via the implementation of a multidisciplinary nutrition support team in the neonatal intensive care unit. Issue 1 (December 2016) - Jeong, Eurim; Jung, Young; Shin, Seung; Kim, Moon; Bae, Hye; Cho, Yoon; Kim, Kwi; Kim, Hyang; Moon, Jin; Kim, Ee-Kyung; Kim, Han-Suk; Ko, Jae
Abstract Background Nutritional support is critical for preterm infants in the neonatal intensive care unit (NICU). A multidisciplinary nutritional support team (NST) that focuses on providing optimal and individualized nutrition care could be helpful. We conducted a thorough evaluation of clinical and nutritional outcomes in a tertiary NICU following the implementation of an NST. Methods This study used a retrospective approach with historical comparisons. Preterm neonates < 30 weeks gestational age or weighing < 1250 g were enrolled. Clinical and nutritional outcomes were compared before and after the establishment of the NST. Medical records were reviewed, and clinical and nutritional outcomes were compared between the two groups. Results In total, 107 patients from the pre-NST period and 122 patients from the post-NST period were included. The cumulative energy delivery during the first week of life improved during the post-NST period (350.17 vs. 408.62 kcal/kg, p  < 0.001). The cumulative protein and lipid deliveries also significantly increased. The time required to reach full enteric feedings decreased during the post-NST period (6.4 ± 5.8 vs. 4.7 ± 5.1 days, p  = 0.016). Changes of Z-score in weight from admission to discharge exhibited more favorable results in the post-NST period (−1.13 ± 0.99 vs.−0.91 ± 0.74, p  = 0.055), and the length of ICU stay significantly decreased in the post-NST period (81.7 ± 36.6 vs. 72.2 ± 32.9 days, p  = 0.040). Conclusions NST intervention in the NICU resulted in significant improvements in the provision of nutrition to preterm infants in the first week of life. There were also favorable clinical outcomes, such as increased weight gain and reduced length of ICU stay. Evaluable data remain sparse in the NICU setting with premature neonatal populations; therefore, the successful outcomes identified in this study may provide support for NST practices.